MECHANICAL SYSTEMS WITH AIR SPRING FLEXIBLE ELEMENTS - Borys VINOGRADOV (Scientific Journal of Silesian University of Technology. Series Transport)
The purpose of this study was to assess the effectiveness of flexible air-spring systems operating in parallel to share the total load, taking into account installation and in-operation errors. This study presented experimental and calculated characteristics of the air spring flexibility and its dependence on the polytropic index and additional volume. It considered patterns of load distribution between the air springs when they are operating in parallel to share the total load for the case when the air springs were used as the supporting elements for various machines and units, and between transmission lines containing flexible couplings, where air springs were installed as flexible elements.